Espiritualidad e hilemorfismo. (2012)
Often today the notion of “soul” is taken to imply a dualistic view of man.Thomas Aquinas conceives of the human soul as a component of the body itself, the “substantial form” that gives the body its very unity. The essay aims to show that, for Thomas, this way of conceiving the human soul is also fundamental for understanding its spiritual nature –its being an incorporeal substance. In order to explain this, Thomas’s approach to the soul’s spirituality is contrasted with that of Descartes. The crucial idea is that of substantial form as “cause of being to matter”.